For the Sake of a Song Wangga Songmen and Their Repertories - Marett, Allan (Indigenous Music, Language and Performing Arts, 2013)
Wangga, originating in the Daly region of Australia's Top End, is one of the most prominent Indigenous genres of public dance-songs. This book is organised around six repertories: four from the Belyuen-based songmen Barrtjap, Muluk, Mandji and Lambudju, and two from the Wadeye-based Walakandha and Ma-yawa wangga groups, the repertories being named after the ancestral song-giving ghosts of the Marri Tjavin and Marri Ammu people respectively. Framing chapters include discussion of the genre's social history, musical conventions and the five highly endangered languages in which the songs are composed. The core of the book is a compendium of recordings, transcriptions, translations and explanations of over 150 song items. Thanks to permissions from the composers' families and a variety of archives and recordists, this corpus includes almost every wangga song ever recorded in the Daly region. There is a separate website associated with this title, http://wangga.library.usyd.edu.au/, and the song repertories can be streamed at http://wangga.library.usyd.edu.au/repertories